Simultaneous Estimation of Multiple Sources of Error in a Smartphone-Based Survey. (7th March 2018) - Antoun, Christopher; Conrad, Frederick G; Couper, Mick P; West, Brady T
Abstract: Although web surveys in which respondents are encouraged to use smartphones have started to emerge, it is still unclear whether they are a promising alternative to traditional web surveys in which most respondents use desktop computers. For sample members to participate in smartphone-based surveys, they need to have access to a smartphone and agree to use it to complete the survey; this raises concerns about coverage and nonresponse, as well as measurement if those who agree to participate have any difficulty using smartphones. In an analysis of data from a smartphone versus desktop (within-subjects) experiment conducted in a probability-based web panel, we compare estimates produced by the smartphone web survey (one condition) and PC web survey (other condition). We estimate mode effects and then examine the extent to which these effects are attributable to coverage, nonresponse, and measurement errors in the smartphone-based survey. While mode effects were generally small, we find that the smartphone web survey produced biased estimates relative to PC web for a subset of survey variables. This was largely due to noncoverage and, to a lesser extent, nonresponse. We find no evidence of measurement effects. Our findings point to the trade-off of the advanced data collection opportunities of smartphones and the potential selection errors that such devices may introduce.